Performance of various distributor designs in a Gas- Solid Fluidized Bed - Mohd Faizal, Mohideen Batcha; Mohd Faizol, Abd Rahman; Fariz, Jaafar; Vijay, R. Raghavan (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.